PENGARUH INTERAKSI TANAH-STRUKTUR PADA TANAH LUNAK TERHADAP DILATASI DARI DUA BANGUNAN TINGGI AKIBAT GEMPA - Sari, Desnila; Murdiansyah, Lukman; Yurisman, Yurisman; Guspari, Oni (Jurnal Ilmiah Poli Rekayasa, 2023)
Earthquakes that occur in buildings can lead to collision force with the next building if the initial gap between the two buildings is not sufficient for its free vibration responses. Collisions can cause amplification of the internal forces in the structural elements and the collision force on the contact zone is usually not considered in the initial design so that it can lead to damage and collapse of buildings. This study aime to determine the effect of Soil-Structure Interaction in the dilatation of two structures in soft soil with consideration of the collision to the next building. The structure is modeled as a structural system with multi degree of freedom (MDOF). The upper structure is considered linear elastic model and does not have damping as well as the lower structure (foundation). The collision can only occur on the floor level of the two buildings in which the contact zone is modeled as an elastic element. The rheological model for Soil-Structure Interaction are taken as a horizontal spring and a rotational spring. Structural dynamic equations was solved by using the Houbolt integration method. The resolution of numerical program was solved by the Matlab software. The results of study showed that soil-strucutre interaction increases the relative displacement under the condition of initial distance (gap) between the two buildings was reduced.